Letters and poems of V. Stus as the material and the spirit of his love story (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article focuses on the intimate poems by Vasyl Stus in the context of this correspondence with loved ones. The comprehension of the loved woman value in the spiritual transformation of the poetical practices and semantic concepts of Stus’ unu-sual interpretation of the myths related with intimate intensiyamy. The influence of the dreams, visions and reminiscences on the determining the main periods of the psycho-logical biography of the poet is studied as well.
Keywords: philosophical masochism; the psychological type of courage; orphism; the other world; the energy of connection/ disconnection; Eros; Qanatos; con-scious love